Investigation of Summer Learning Loss in the UK—Implications for Holiday Club Provision - Shinwell, Jackie; Defeyter, Margaret Anne (Frontiers in Public Health, 2017)
This study sought to examine whether summer learning loss occurs in spelling and word reading in a population of 77 primary school aged children aged between 5 and 10 years (37 boys, mean age 100 months, SD 18 months, and 40 girls mean age 103 months, SD 16 months) attending three schools in areas of low socioeconomic status in Scotland and the North East of England. Word reading and spelling was measured using the word reading and spelling subtests of the Wide Ranging Achievement Test. Participants were tested on three occassions: immediately before and immediately after a 7-week summer break, and again after 7-weeks of teaching. The results showed a significant main effect of time for spelling scores, F(2,136) = 21.60, p < 0.001, ηp2=0.241. Post-hoc analysis [t(73) = 4.84, p ≤ 0.001] showed that spelling scores were significantly higher at the end of the summer term (M = 26.57) than at the start of the new academic year (M = 25.38). Likewise, spelling scores after 7 weeks post return to school (M = 27.61) were significantly higher than at the start of the Autumn term, t(73) = 7.79, p ≤ 0.001. Performance in spelling declined when children returned to school immediately after the summer holiday (M = 25.38) but 7 weeks later, performance had improved beyond the baseline reported immediately before the summer break (M = 26.57) [t(73) = 4.40, p ≤ 0.001]. There was also a main effect of school in relation to spelling scores, [F(2,68) = 6.49, p < 0.05, ηp2=0.160], with children from school 2 and school 3 outperforming children from school 1. There was no signficant main effect of gender [F(1,68) = 1.47, p > 0.05, ηp2=0.021]. None of the interactions were significant. There was no main effect of time on word reading scores [F(2,136) = 1.12, p ≥ 0.05, ηp2=0.016]. However, there was a main effect of school [F(2,68) = 4.85, p ≤ 0.01, ηp2=0.125] in relation to reading scores, with children from school 2 and school 3 outperforming children from school 1. There was no significant main effect of gender [F(1,68) = 0.37, p ≥ 0.05, ηp2=0.005]. None of the interactions were significant. This is the first such study in the UK to demonstrate that after a summer break of seven weeks, summer learning loss occurred, or at least stagnation in learning, in a population of primary school aged children attending schools in areas of low SES in relation to spelling. However, after seven weeks of teaching, children caught up to and exceeded the level achieved in spelling prior to the summer break. However, the summer holiday period did not result in a loss of word reading skill, reading scores were consistent across the entire study.